Peran Penggunaan E-Wallet dalam Membentuk Kebiasaan Keuangan Generasi Z Pada Siswa SMA Triguna 1956 Jakarta - Aulia Rahma Salsadillah; Hanum Cahya Ramadanty; Nadifa Aulia Tatangin; Yeni Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The development of digital payment technology, particularly electronic wallets (e-wallets), has brought about significant changes in people's financial behavior and habits, particularly among Generation Z. The convenience, speed, and diverse features offered by e-wallets have made them one of the most widely used digital financial instruments among students. However, e-wallet use without good financial understanding and habits has the potential to encourage consumptive behavior and imprudent financial management. This Community Service (PKM) activity aims to improve the understanding of Triguna 1956 Jakarta High School students regarding the role of e-wallet use in developing healthy, wise, and responsible financial habits among Generation Z. The activity's implementation methods included outreach, educational material delivery, interactive discussions, and evaluation of participant understanding. The results of the activity showed an increase in students' knowledge of the basic concepts of e-wallets, awareness of the benefits and risks of using them, and understanding of how to build more controlled and responsible financial habits. This activity is expected to contribute to the sustainable strengthening of digital financial literacy among high school students. Keywords: Wallet, Fintech, Financial Habits, Generation Z, Digital Financial Literacy, Community Service.